Gambaran Intimacy ditinjau dari Gaya Resolusi Konflik Pada Wanita Minang yang Mengalami KDRT - Rida Yanna Primanita; Yuninda Tria Ningsih (Psikoislamika: Jurnal Psikologi Islam, 2021)
Abstract: The research aims to determine the description of intimacy based on conflict resolution styles in Minang women who experience domestic violence. The type of this research is comparative quantitative. It analyzes using the Kruskal-Walli’s difference test techniques. The population of this research were married women who experienced domestic violence in West Sumatra, using purposive sampling technique with the characteristics of Minang ethnic women, aged 21- 40 years, married 10 years, had children, lived together. The research instrument used was the Intimacy scale from Stenberg's love triangle theory and a conflict resolution style scale based on the dimensions and indicators stated by Sillars and Zietlow. Based on the result, it was obtained that the value of Sig = 0.013 (Sig 0.05), which means that there is a difference in intimacy based on the conflict resolution style of Minang women who experience domestic violence in West Sumatra.Keywords: Intimacy; conflict resolution style; Minang women; domestic violenceAbstrak: Penelitian ini bertujuan untuk memaparkan gambaran intimacy ditinjau dari gaya resolusi konflik pada wanita yang mengalami KDRT. Penelitian ini berjenis kuantitatif komparatif dan dianalisa menggunakan teknik uji beda Kruskal-Wallis. Populasi penelitian ini yakni wanita menikah yang mengalami KDRT di Sumatera Barat, dengan teknik pengambilan sampel purpusive sampling dengan ciri wanita etnis Minang, berusia 21-40 tahun, usia pernikahan 10 tahun, memiliki anak, tinggal bersama. Instrumen penelitian yang digunakan skala Intimacy dari teori segitiga cinta stenberg dan skala gaya resolusi konflik berdasarkan dimensi dan indikator yang dinyatakan oleh Sillars dan Zietlow. Berdasarkan hasil perhitungan diperoleh nilai Sig =0,013 (Sig0,05), yang berarti terdapat perbedaan intimacy ditinjau dari conflict resolution style pada wanita Minang yang mengalami kekerasan dalam rumah tangga di Sumatera Barat.Kata kunci: Intimacy, gaya resolusi konflik, wanita Minang, KDRT